Chemistry Practical Book : Chemistry Practical for students of all Universities of India - Jain, Preeti; Bhawsar, Jeetendra; Sidhwani, Hitendra Kaur (New Delhi: Indu Book Services, 2024)
The presentation of the text of the book is simple and concise. It has been presented in a lucid manner so that the students may develop interest in the chemistry practical's and may face viva-voce boldly. The language of the book is simple so that it may be in the reach of even an ordinary English knowing student. The book is complete in all aspects and very useful to students and professors. The authors believe that the book will largely meet the required demands of students of Science and Engineering.
Keywords: Chemistry Practical book -- Experiment